Extrahepatic portal venous laceration in TIPS treated with stent graft placement - Krajina, A; Hulek, P; Ferko, A; Nozicka, J (Hepato-gastroenterology, 1997)
Three cases of intraperitoneal bleeding from extrahepatic portal vein laceration were observed in a series of 104 patients with TIPS. In one patient, bleeding continued after Wallstent placement and the patient died during an emergency laparotomy. Bleeding was stopped in the other two patients by using a stent graft rather than a regular stent. One shunt remained patent and outflow stenosis developed in 3 months. The other shunt thrombosed in 5 months. Both shunts were fully reopened.
Keywords: mužské pohlaví; Male; senioři; Blood Vessel Prosthesis; Stents; cévní protézy; Humans; stenty; lidé; vena portae; mladiství; Portasystemic Shunt, Transjugular Intrahepatic; peroperační komplikace; Adolescent; Radiography; transjugulární intrahepatální portosystémový zkrat; Portal Vein; Hemoperitoneum; Intraoperative Complications; dospělí; radiografie; Adult; hemoperitoneum; Aged